ANALISIS KEDUDUKAN HUKUM UMRAH MANDIRI DALAM KERANGKA REGULASI INDONESIA - Kristiane, Desy; Nadia, Nadia (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2024)
This study examines the legal position of independent Umrah (Umrah Mandiri/ Umrah Backpacker) within the regulatory framework in Indonesia, with a focus on Law No. 8 of 2019 concerning Hajj and Umrah Services. Independent Umrah, which refers to performing Umrah without engaging a travel agency (PPIU), has gained popularity due to its perceived efficiency and flexibility. However, this practice is not specifically regulated under the current legal framework, leading to various risks, including visa administration issues and limited legal protection. The study employs a normative juridical approach with an analysis of statutory provisions to evaluate the adequacy of existing regulations in addressing the phenomenon of Independent Umrah. The findings highlight the need to strengthen regulations to provide legal certainty and adequate protection for independent Umrah pilgrims, while maintaining the essential oversight and protective role of the state